2002
DOI: 10.1258/0022215021910753
|View full text |Cite
|
Sign up to set email alerts
|

Fever and acquired torticollis in hospitalized children

Abstract: Acute torticollis due to non-traumatic atlanto-axial subluxation (AAS) is often seen in children presenting with inflammatory conditions of the upper respiratory tract and the neck. Grisel's syndrome is the eponym given to this condition. These patients may present earlier in the disease process without evident subluxation. Thus, early recognition of the condition with prompt commencement of appropriate conservative treatment could halt the progression into Grisel's syndrome. The purpose of this study is to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
1
22
0
1
Order By: Relevance
“…All studies agree that any patient with neurologic symptoms should undergo immediate open fixation. A study of 20 patients with AAS performed at the Children's Hospital of Pittsburgh showed a 70% success rate for conservative management with hard cervical collars with or without traction [13]. Also of note, there was a lower success rate noted for patients who had AAS for longer than 3 weeks, which agrees with previously published studies.…”
Section: Discussionsupporting
confidence: 84%
“…All studies agree that any patient with neurologic symptoms should undergo immediate open fixation. A study of 20 patients with AAS performed at the Children's Hospital of Pittsburgh showed a 70% success rate for conservative management with hard cervical collars with or without traction [13]. Also of note, there was a lower success rate noted for patients who had AAS for longer than 3 weeks, which agrees with previously published studies.…”
Section: Discussionsupporting
confidence: 84%
“…Inflammatory torticollis (stiffness, rigidity, and torsion) is generally caused by swollen lymph nodes due to external injuries or cold (Mezue et al 2002), but the causes remain unclear in many cases. Mild cases can be cured by a few days' rest; however, when the symptoms fail to i m p r o v e , n e c k t r a c t i o n m a y b e n e e d e d (Bredenkamp and Maceri 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory torticollis is caused by muscle contracture or swollen lymph nodes from external injuries or cold, and sets up stiffness, rigidity, and torsion of neck (Bredenkamp and Maceri 1990;Mezue et al 2002).…”
Section: History Of Eventsmentioning
confidence: 99%
“…The subluxation usually appears after a previous period of torticollis and fever. This period, with rotational deformity but without subluxation, is of great importance [14] because it is during this initial period of time when conservative therapy can be undergone (analgesia, immobilization, and rest). If the muscle spasm persists over 24 h, diazepam can be added to the treatment until improvement.…”
Section: Introduction and Historical Overview Of The Disordermentioning
confidence: 99%